2019
DOI: 10.1136/bmjopen-2018-026031
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes associated with peripherally inserted central catheters in hospitalised children: a retrospective 7-year single-centre experience

Abstract: ObjectivesThe use of peripherally inserted central catheters (PICCs) are an integral part of caring for hospitalised children. We sought to estimate the incidence of and identify the risk factors for complications associated with PICCs in an advanced registered nurse practitioners (ARNP)-driven programme.DesignRetrospective cohort study.SettingSingle-centre, large quaternary children's hospital.ParticipantsHospitalised children who had PICC inserted from 1 January 2010 to 31 December 2016.InterventionsNone.Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 31 publications
0
26
1
2
Order By: Relevance
“…However, still, there is room to improve our first attempt success rate in the coming years. Exceptionally, only 1%–2% of our babies needed more than three attempts for ECC insertion compared to 7.3% in another study by Badheka et al 17 …”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…However, still, there is room to improve our first attempt success rate in the coming years. Exceptionally, only 1%–2% of our babies needed more than three attempts for ECC insertion compared to 7.3% in another study by Badheka et al 17 …”
Section: Discussioncontrasting
confidence: 62%
“…However, still, there is room to improve our first attempt success rate in the coming years. Exceptionally, only 1%-2% of our babies needed more than three attempts for ECC insertion compared to 7.3% in another study by Badheka et al 17 Because of the successful ECC team implementation, the number of SCVCs gradually decreased to zero in 2018. That saved considerable extra effort, cost, and time.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Song et al examined 549 hospitalized patients aged 66-104 years who were undergoing PICCs placement, and found a history of thrombosis, large number of lumens, and wide-gauge catheters were strong risk factors for patients aged >65 years undergoing PICCs placement (37). To estimate the incidence of and identify the risk factors for complications associated with PICCs, Badheka et al (38). studied 2,558 hospitalized children, and suggested that younger children (<5 years old) were at an increased risk of developing PICCs related central line-associated bloodstream infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although, PICCs are preferred over other large central vein catheters in a convalescing child, they are not trivial procedures and are associated with significant morbidity. 2 The apparent benefits of the transdiaphragmatic TBC are very encouraging, but before its more widespread adoption, a full assessment of countermeasures is necessary. The current analysis looks at complications related to removal and dislodgement of TBCs and transthoracic lines, but not other complications associated with central lines such as thrombus and infection.…”
mentioning
confidence: 99%